Data insertion and archiving in erasure-coding based large-scale storage systems - Pamies-Juarez, Lluis (2013)
Given the vast volume of data that needs to be stored reliably, many data-centers and large-scale file systems have started using erasure codes to achieve reliable storage while keeping the storage overhead low. This has invigorated the research on erasure codes tailor made to achieve different desirable storage system properties such as efficient redundancy replenishment mechanisms, resilience against data corruption, degraded reads, to name a few prominent ones. A problem that has mainly been overlooked until recently is that of how the storage system can be efficiently populated with erasure coded data to start with. In this paper, we will look at two distinct but related scenarios: (i) migration to archival -leveraging on existing replicated data to create an erasure encoded archive, and (ii) data insertion - new data being inserted in the system directly in erasure coded format. We will elaborate on coding techniques to achieve better throughput for data insertion and migration, and in doing so, explore the connection of these techniques with recently proposed locally repairable codes such as self-repairing codes.